FLAVONOIDS IN ACACIA CATECHU BARK EXTRACTS AND BIBLIOGRAPHIC ANALYSIS IN GUNA, MADHYA PRADESH, INDIA - TIWARI, ARCHANA; TIWARI, AVINASH (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: The objective of this work is to examine the overall flavonoid content in bark samples of Acacia catechu obtained from the Guna region of Madhya Pradesh, India, using several extraction methods. Furthermore, this study has incorporated current literature, conducted bibliographic analysis, examined co-authorship studies, and gathered other pertinent material to augment comprehension and underscore the importance of the research. Methods: For the purpose of this experiment, a total of thirty samples of test plants were gathered from the research region throughout various seasons. Each individual sample was prepared with six different solvents. Following this, a standardized laboratory technique was used to undertake quantitative testing. The bibliographic analysis was conducted using Dimension AI and VOS viewer software in the timeframe of 1975-2024 (till March 8, 2024). Results: Findings indicated that the polar organic solvents methanol, ethanol, acetone, and the aqueous extracts were shown to display a substantial quantity of flavonoids, chloroform extracts exhibited negligible and benzene extracts were found to be entirely devoid of the same. The comparative bibliographic investigations have confirmed the need to study the possible medicinal properties of test plants in the Guna region. Conclusion: This preliminary study has the potential to identify new, economically viable, and readily available sources of flavonoids, which are natural antioxidants present in the indigenous flora of the Guna region.